2022
DOI: 10.3390/biology11060896
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Metacognitive and Psychological Factors in Learning-Induced Plasticity of Resting State Networks

Abstract: While resting-state networks are able to rapidly adapt to experiences and stimuli, it is currently unknown whether metacognitive processes such as confidence in learning and psychological temperament may influence this process. We explore the neural traces of confidence in learning and their variability by: (1) targeting rs-networks in which functional connectivity (FC) modifications induced by a learning task were associated either with the participant’s performance or confidence in learning; and (2) investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…Expanding on previous studies that showed that the basal cerebral state, as indexed by intrinsic FC, is modified in the short term after the brain has been engaged in consolidating learned action-outcome contingencies [23,24,27,[29][30][31]44], the present study showed that it also occurs after being engaged in the remapping of previously learned action-outcome contingencies. Moreover, as we speculated previously [23], modifications in intrinsic regional connectivity differed depending on the behavioral tendencies adopted by the participants when facing unexpected changes in the environment.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Expanding on previous studies that showed that the basal cerebral state, as indexed by intrinsic FC, is modified in the short term after the brain has been engaged in consolidating learned action-outcome contingencies [23,24,27,[29][30][31]44], the present study showed that it also occurs after being engaged in the remapping of previously learned action-outcome contingencies. Moreover, as we speculated previously [23], modifications in intrinsic regional connectivity differed depending on the behavioral tendencies adopted by the participants when facing unexpected changes in the environment.…”
Section: Discussionsupporting
confidence: 56%
“…The ACC is implicated in the evaluation of feedback and would promote either exploration in the case of negative feedback or exploitation if the feedback is positive [6]. Additionally, it is well-established that the cerebellum is engaged in motor learning processes, and there is increasing evidence that this is the case for cognitive tasks as well [22], notably in the building of internal models of stimuli-response associations [23]. The cerebellum, via cortico-cerebellar circuits, may also participate in the exploration/exploitation trade-off.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations